الفقه المالكي في السنغال: الانتشار والتطور - سعيد جاه ومحمد الطاهر الميساوي = The dissemination and development of the Maliki jurisprudence in Senegal - Dia, Seydou; El-Mesawi, Mohamed El-Tahir (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
Islam reached sub-Saharan Africa early on by means of Islamic conquests that swept Africa from north to east. The Berbers at that time had all credit for spreading Islam in Sub-Saharan Africa, including Senegal. This paper accounts for a brief historical background and how Maliki jurisprudence is disseminated all over the Republic of Senegal. Senegal is situated in West Africa, where more than eighty scholarly circles, based on the teaching of Maliki jurisprudence, are spread out along the flanks of the Fulani on the banks of the Senegalese river from the heights of Fouta Djallon. These scholarly circles or schools, established by Senegalese jurists and scholars in the region and as time passed, turned from local institutions into becoming centers of learning for many international students coming from outside the country to seek knowledge. This is mostly due to the great reputation and accreditation those scholars had acquired over the years by traveling around the Islamic world to disseminate their knowledge and thoughts in places such as Hijaz (Saudi Arabia) and Morocco. This paper uses a combination of descriptive and historiographical approach to fulfil the objectives set by the study. In the end, it concludes by making some recommendations and suggestions for future studies.